The Use of Pulsed Field Gel Electrophoresis in Listeria monocytogenes Sub-Typing - Harmonization at the European Union Level - Felix, Benjamin; Dao, Trinh Tam; Lombard, Bertrand; Brisabois, Adrien Assere Anne; Roussel, Sophie (IntechOpen, 2012)
None